Obesity-Related Glomerulopathy: A Latent Change in Obesity Requiring More Attention - Shuting Yang; Chuqing Cao; Tuo Deng; Zhiguang Zhou (Karger Publishers, 2020)
Background: Obesity has become a major public health problem, and the prevalence of kidney diseases has increased in parallel. Among kidney diseases caused by metabolic disorders, obesity-related glomerulopathy (ORG) is secondary to obesity. Summary: ORG is mainly caused by glomerular hyperfiltration, dysregulation of hormone and cytokine secretion in adipose tissues, and ectopic lipid accumulation in renal cells. ORG is pathologically characterized by glomerular hypertrophy, with or without focal and segmental glomerulosclerosis. Patients with ORG usually present with proteinuria concomitant with metabolic disorders such as dyslipidemia and hypertension. Weight loss, RAAS inhibitors, and improved insulin resistance can reduce the progression of ORG. Conclusion: ORG is a growing renal pathological change in obese individuals, and a comprehensive understanding of the disease is pivotal to avoid its occurrence and improve quality of life for those with obesity. Key Messages:This review comprehensively describes the characteristics of ORG in pathological changes, clinical manifestations, pathogeneses and treatments.